PROFIL KEMAMPUAN MOTORIK SISWA SEKOLAH DASAR NEGERI 03 BINUANG KAMPUNG DALAM KOTA PADANG - Mustaqim, Arrafi; Arsil; Bakhtiar, Syahrial; Marta, Ibnu Andli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study was the lack of information regarding the motor ability level of students at SD Negeri 03 Binuang Kampung Dalam. Therefore, this study aimed to determine the motor ability level of the students.This study employed a quantitative descriptive research design using a survey method. Data were collected through tests and measurements. The population consisted of 283 students of SD Negeri 03 Binuang Kampung Dalam. The sample comprised 60 students, including 30 boys and 30 girls. The instrument used was the Motor Ability Test, which had a validity coefficient of 0.87 and a reliability coefficient of 0.93. The test battery included a 4 × 10-meter shuttle run, a ball throw-and-catch test against a wall from a distance of 1 meter, the Stork Stand Positional Balance Test, and a 30-meter sprint test. The data were analyzed using descriptive statistical analysis with percentage calculations.The results showed that the students' motor ability was classified as very good for 6.67% (4 students), good for 25.00% (15 students), fair for 45.00% (27 students), poor for 21.67% (13 students), and very poor for 5.00% (3 students). Overall, the motor ability of the students at SD Negeri 03 Binuang Kampung Dalam was categorized as fair.